2013
DOI: 10.1111/cup.12256
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic concordance rates in the subtyping of basal cell carcinoma by different dermatopathologists

Abstract: Journal of Cutaneous PathologyDiagnostic concordance rates in the subtyping of basal cell carcinoma by different dermatopathologists Background There are numerous subtypes of basal cell carcinoma (BCC). Defining the histopathologic subtype is an essential element in patient management, but there is little known data regarding interobserver precision in subtyping BCC. Methods We studied interobserver variance between six board-certified dermatopathologists who subtyped 100 BCCs in a blinded fashion. We used kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…In line with Nedved et al ., we observed a somewhat lower level of agreement on BCC subtyping than on BCC presence . This is logically explained because BCC presence (yes or no) is a binary question while the differentiation between BCC subtypes is less strict and mixed subtypes are common.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In line with Nedved et al ., we observed a somewhat lower level of agreement on BCC subtyping than on BCC presence . This is logically explained because BCC presence (yes or no) is a binary question while the differentiation between BCC subtypes is less strict and mixed subtypes are common.…”
Section: Discussioncontrasting
confidence: 58%
“…In line with Nedved et al, we observed a somewhat lower level of agreement on BCC subtyping than on BCC presence. 23 This is logically explained because BCC presence (yes or no) is a binary question while the differentiation between BCC subtypes is less strict and mixed subtypes are common. To improve the diagnostic concordance in BCC subtyping, it might be necessary to further specify and simplify the current World Health Organization classification of BCC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 66 BCC subtypes are described in the scientific literature. A recent study suggested a simplified classification to aid clinical decision making in the superficial, fibroepithelial, nodular and infiltrative subtypes . Superficial BCCs (sBCCs) are considered to be the least aggressive subtype, as they do not tend to invade deeply in the dermis.…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose of this study, we selected a set of representative samples of cutaneous BCCs included four histomorphological subtypes: superficial (8 cases), nodular (12 cases), mixed nodular-infiltrative (10 cases), and infiltrative (8 cases). Further, according to the previous reports (13,14) and recommendations proposed recently by The Royal College of Pathologists (15), they were divided into two separate subgroups for statistical analysis. The first subgroup comprised 20 low-risk (non-infiltrative) BCC subtypes (superficial and nodular).…”
Section: Clinicaldataandtumorspecimensmentioning
confidence: 99%